LC–MS profiling, in vitro and in silico C-ABL kinase inhibitory approach to identify potential anticancer agents from Dalbergia sissoo leaves - Hem N. Naik; Dilip Kanjariya; Shahnaz Parveen; Iqrar Ahmed; Abha Meena; Harun Patel; Ramavatar Meena; Smita Jauhari (Scientific Reports, 2024)
Abstract Belonging to the Fabaceae family, Dalbergia sissoo, a versatile plant, has gained prominence for its potent medicinal attributes, especially antipyretic, anti-inflammatory, and cardioprotective properties, as well as the use of its leaf juice in cancer treatment. Despite these recognized applications by natives and tribals, comprehensive insight into its biological activities and chemical composition remains limited. This study aimed to explore the cytotoxic potential of sequentially extracted leaf extracts from Dalbergia sissoo using various solvents, aiming to unveil the array of phytochemicals through LC–MS profiling. Among the extracts evaluated, the extract employing methanol:water extracting media (HN-2) appeared with the most remarkable results in both phytochemical diversity and biological activity. Furthermore, in vitro results of HN-2's in vitro anticancer efficacy were confirmed through in silico molecular docking and molecular dynamics simulation. These analyses demonstrated its ability to inhibit C-ABL kinase within leukemia K562 cells, directing that Dalbergia sissoo leaves serve as a bioactive agent reservoir. Consequently, this suggests that the Dalbergia sissoo plant is a potential source of bioactive compounds that can be used as a precursor for developing new cancer inhibitors, mainly targeting leukemia.